PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 BASA AMPEK BALAI TAPAN TAHUN PELAJARAN 2013/2014 - Hardianto, Hardianto; Edriati, Sofia; febriana, Rina (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ TheÂ background of this research is that the students mathematical concept apprehensions are low and the students like to ask to her friends reather than to teachers. So low students learning out comes VIII-grade of SMPN 1 Basa Ampek Balai Tapan of year 2013/2014. The purpose of this research is to know whether the students mathematical concept apprehensions by applying the snowball throwing cooperative learning model is better than using the conventional learning for the VIII-grade students of SMPN 1 Basa Ampek Balai Tapan. This is experimental research with random to subject design. The population in this research is the VIII-grade students of SMPN 1 Basa Ampek Balai Tapan. The technique of sample classes were determined randomly. The instrument used in this research is test for the mathematical concept apprehension. Based on the result of data analysis, it is know that both sample classes distribute normally and homogenously. So that the hypothesis is accepted, that means that the students mathematical concept apprehension. Using the snowball throwing cooperative learning model is better than that using the conventional learning for the VIII-grade students of SMPN 1 Basa Ampek Balai Tapan